QS1: Pre-implanted Nerve Grafts (PING) to Improve Functional Outcomes in VCA. (July 2021) - von Guionneau, Nicholas; Liu, Xiuyun; Slavin, Benjamin; Finkelstein, Emily; Yoon, Joshua; Lee, Erica; Kothari, Ruchita; Glass, Connor; Khoo, Kimberly; Kohler, Raymond; Hoke, Ahmet; Shores, Jamie; et al.
Abstract : Purpose: Improved graft reinnervation and functional recovery would greatly enhance the utility of vascularized composite allotransplantation (VCA). Pre-implantation of nerve grafts in a limb transplant recipient prior to transplantation to increase the length of the severed nerves in the amputation stump offers a novel, readily translatable approach to this problem. At the time of transplantation a pre-implanted nerve graft (PING) would be elevated from its wound bed in the amputated stump and unfurled distally into the transplanted limb, allowing for a more distal nerve coaptation. Methods: We used a reversed sciatic-tibial nerve isograft coapted end-to-end to a median nerve in a rat to: (1) determine viability of distal axons after elevating PINGs; and (2) assess for ischemic injury to axons in the distal PING following elevation from the wound bed. For axonal viability, grafts of varying lengths (2cm, 3cm, 4cm, n≥5/group) were left to regenerate for 8 weeks. The distal ends were then biopsied prior to elevation, and again one week after elevation. For ischemia assessment, blood flow along 4cm long PINGs was measured with laser doppler at multiple timepoints: baseline (at time of grafting), 8 weeks after grafting (before elevation), immediately after elevation, and 3 and 7 days post-elevation (n=8/timepoint). Means were compared with t-tests and ANOVA. A pig forelimb model was used to assess the functional impact of PINGs. A 6cm long reversed ulnar-PING was coapted to the proximally transected ulnar nerve. After 12 weeks of regeneration, the distal PING was transferred end-to-end to the median nerve just proximal to the elbow. A control group underwent ulnar-to-median nerve transfer 6cm proximal to the elbow (n=4 limbs/group). Hoof flexion force was measured every three weeks. Results Axonal viability: after 8 weeks, axons had regenerated into the distal grafts in all lengths: mean myelinated axon counts (±SD): 7043 (±790), 6066 (±1838), 6491 (±983) in 2cm, 3cm, 4cm grafts, with no differences between graft lengths (p=0.48). One week after elevation and unfurling, the number of myelinated axons was significantly decreased in all groups (p<0.006): 3821 (±567), 2953 (±1107), 2894 (±1761) in 2cm, 3cm, 4cm grafts, with no differences between lengths (p=0.91). Ischemic injury: immediately after elevating a PING, blood flow within the distal half of the graft fell to baseline levels (i.e. no blood flow). 3 days after elevation, blood flow throughout the graft was significantly above baseline (p⩽0.04) and matched/exceeded flow measured immediately prior to elevation. Functional impact: preliminary results suggest PINGs can deliver rapid functional recovery. Conclusions: Axons remain present in clinically relevant numbers at the distal ends of PINGs after elevation and unfurling. A decrease in axon counts after elevation may relate to ischemia in the distal PING immediately after elevation. Preliminary functional results show PINGs are capable of delivering early functional recovery .